A Numerical Study on the Environmental Vibration in Surrounding Buildings Induced by Freight Train Operations - Choe, Changhyon; Jong, Kwanghyok; Choe, Chungil; Kang, Cholhyok; Ko, Daehyok (Disaster in Civil Engineering and Architecture, 2026)
The proliferation of railway systems in urban areas has heightened concerns regarding ground-borne vibrations and their impact on adjacent structures. This study presents a comprehensive numerical framework for predicting building vibrations induced by freight train traffic, addressing a gap in vehicle-specific analyses. A coupled modeling approach is employed, integrating multi-body dynamics and finite element methods. The vehicle-track interaction for a 60-ton freight wagon is simulated using the multi-body dynamics software SIMPACK to obtain the dynamic axle loads. These loads are then applied to a detailed 3D finite element model, developed in ANSYS, that captures the track-soil-building interaction, including nonlinear contact at the foundation-soil interface. The model is used to evaluate the Vibration Acceleration Level (VAL) within a building and to conduct a sensitivity analysis on key parameters. The results indicate that the vibration level decreases significantly with increasing distance from the railway, with an attenuation rate consistent with empirical laws for surface waves. A parameter study revealed that a ±20% variation in soil shear wave velocity can alter predicted VAL by up to 5 dB. At a distance of 20 m, the predicted VAL was found to satisfy standard building vibration limits for the modeled scenario. Furthermore, the vibration response was non-uniform within the building and exhibited a complex, non-monotonic relationship with train speed, indicative of critical speed effects.